An investigative study into the workload of air traffic controllers in simulators - Liao, Weiliang (2016)
Air traffic controllers are the “eyes” of the pilots in the skies. Without them, the pilots would not be able to fly to his destination safely and expeditiously. As the demand for air travel increases, more aircrafts are flying in a particular airspace at a specific time. As such, workload of these air traffic controllers will tend to increase as they will have more aircrafts to control. However, there are numerous workload measurement techniques utilizing different methods to measure the workload of an air traffic controller. Hence, this could be a potential problem as there are huge variations in terms of the results collected. This report aims to look at the performance of air traffic controllers, thereafter zooming in to how air traffic complexity is correlated to their performance and workload. Real time simulations will be conducted to determine how the various air traffic complexity factors will affect the workload of the air traffic controller. Workload measurement techniques will also be explored in depth and used to measure the workload performance. This report will then analyze the data collected from the simulations and discuss on the modified workload model developed that will be used to evaluate the workload performance of air traffic controller. Lastly, recommendations will be provided to further improve on the modified workload model to further enhance the robustness.